2019
DOI: 10.1097/md.0000000000016531
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between mechanical power, transforming growth factor-β1, and connective tissue growth factor levels in acute respiratory distress syndrome patients and their clinical significance in pulmonary structural remodeling

Abstract: Background: To identify the clinical correlations between mechanical power and transforming growth factor-β1 (TGF-β1) and connective tissue growth factor (CTGF) in acute respiratory distress syndrome (ARDS) patients, their clinical significance in pulmonary structural remodeling in ARDS patients was investigated. Methods: Ninety-five patients with moderate or severe ARDS, who required mechanical ventilation therapy, were randomly selected among hospitalized patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Animal experiments showed that the level of TGF-β1 in ARDS model rats increased significantly, indicating that it may be involved in the early inflammatory response and suggesting that TGF-β1 plays an important role in pulmonary dysplasia and ARDS interstitial fibrosis [ 17 ]. Recent studies have found that TGF-β1 induces collagen-soluble protein gene expression, leading to collagen curling and fibroplasia, indicating that TGF-β1 plays an important role in the early lung injury and fibroplasia of ARDS [ 18 ]. In infants with infantile respiratory distress syndrome, who may develop chronic lung disease, the level of TGF-β1 activity is 6 times that of other children, and those with high levels of TGF-β1 are associated with higher mortality and shorter survival time [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments showed that the level of TGF-β1 in ARDS model rats increased significantly, indicating that it may be involved in the early inflammatory response and suggesting that TGF-β1 plays an important role in pulmonary dysplasia and ARDS interstitial fibrosis [ 17 ]. Recent studies have found that TGF-β1 induces collagen-soluble protein gene expression, leading to collagen curling and fibroplasia, indicating that TGF-β1 plays an important role in the early lung injury and fibroplasia of ARDS [ 18 ]. In infants with infantile respiratory distress syndrome, who may develop chronic lung disease, the level of TGF-β1 activity is 6 times that of other children, and those with high levels of TGF-β1 are associated with higher mortality and shorter survival time [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, MP may become the new standard to perform lung-protective ventilation in ARDS patients [5]. Studies have shown that when MP exceeds 17 J/min, the 28-day mortality in patients increases significantly, which indicated that the level of MP is related to the prognosis of patients and may be related to the severity of ARDS [6,7]. Whether spontaneous respiration in ARDS is helpful or harmful remains an area of debate [8].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a correlation between power and serum fibrosis biomarkers has been found in ARDS patients. [ 20 ]…”
Section: Mechanical Power As a Promising Indicator Of Vilimentioning
confidence: 99%